1996
DOI: 10.1038/bjc.1996.572
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Kaposi's sarcoma in the Nordic countries before the AIDS epidemic

Abstract: Summary Based on data from the Nordic cancer registries, time-related trends in incidence of Kaposi's sarcoma (KS) were analysed in four ethnically similar populations before the AIDS epidemic. Data were available for different time periods in Denmark (1970-79), Sweden (1958-79), Finland (1953 and Norway (1953-79). KS was more common among men than among women aged 60 years or more, whereas no differences were observed for younger persons. The incidence of KS differed significantly between the four countries (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Among the age group of 0 -24, the rates per million were 0.6 and 0.2 in males and females, respectively, with no cases recorded below 5 years of age (Table 2). The substantial increase with age in the age-specific rates of CKS cases is consistent with other reports (Cottoni et al, 1996;Hjalgrim et al, 1996;Brenner et al, 2002).…”
Section: Resultssupporting
confidence: 81%
“…Among the age group of 0 -24, the rates per million were 0.6 and 0.2 in males and females, respectively, with no cases recorded below 5 years of age (Table 2). The substantial increase with age in the age-specific rates of CKS cases is consistent with other reports (Cottoni et al, 1996;Hjalgrim et al, 1996;Brenner et al, 2002).…”
Section: Resultssupporting
confidence: 81%
“…However, in a recent study of classical KS in four Nordic countries (Sweden, Norway, Finland and Denmark) before the AIDS epidemic, we reported that highly significant variation in incidence amounting to eightfold in women and 13-fold in men may also exist between four ethnically very similar, neighbouring populations (Hjalgrim et al, 1996b). As this variation could not be attributed to any known risk factor for classical KS, including proportion of immigrants from high-risk areas, transplantations, diagnostic or registrational procedures, it may suggest the existence of an environmental factor of significance for the development of KS (Hjalgrim et al, 1996b).Intrigued by the variation in KS incidence between these four countries, we ascertained the incidence of classical KS in two other geographically distinct Nordic populations, Iceland and the …”
mentioning
confidence: 73%
“…In these countries world standardized rates varied from 0.01 to 0.09 per 100 000 person-years in women and from 0.02 to 0.26 per 100 000 person-years in men (Figure 1) (Hjalgrim et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third group included a population-based sample of healthy individuals from northern Sweden, who were positive for anti-lytic or anti-latent KSHV antigens [7]. Since the incidence of classical KS in northern Sweden is estimated to be four-fold lower than in Italy [8], we wanted to check whether these individuals have elevated levels of anti-KCP antibodies compared to previously studied groups of Italian patients. This could suggest possible role of anti-KCP response in protection from KS development.…”
Section: Introductionmentioning
confidence: 99%